Mengukur kepercayaan masyarakat atas kinerja Kementerian ATR/BPN melalui analisis sentimen pada platform digital - Reza Nur Amrin; Ridho Darman; Asih Retno Dewi; Sudibyanung Sudibyanung (Sekolah Tinggi Pertanahan Nasional, 2026)
Governments increasingly leverage social media for institutional reputation management, yet a significant gap often persists between institutional narratives and public perception. This study aims to analyze the topical and sentimental disparities between the Instagram posts of Indonesia’s Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and netizens' responses throughout 2023. Employing a quantitative approach, this research applies lexicon-based sentiment analysis and descriptive content analysis to 15,198 comments across 1,213 posts. The results reveal a striking digital communication paradox. While the institutional agenda is heavily dominated by the celebration of land certificate handovers and ministerial visits, 56.5% of public comments exhibit negative sentiment. Netizens actively repurpose the comment section into a grassroots grievance mechanism for agrarian disputes, bureaucratic hurdles in land certification, and reports of land mafias. Consequently, there is a diametrical clash in the contextualization of the core lexicons